The Yamuna Expressway - Raghuram, G., 1955-; Mehta, Pranav (London : Indian Institute of Management, Ahmedabad, 2011)
It was December 13, 2010. The Government of Uttar Pradesh announced their plan to urbanize the entire area along the Yamuna Expressway (YE) in order to prevent the haphazard growth of urban sprawls on the flanks of the YE. The YE was conceived in 1997 as a dream project of Ms Mayawati, the then Chief Minister of Uttar Pradesh, with the idea of reducing the travel time between Delhi (and the larger National Capital Region) and Agra. It was a 165 kilometres long expressway and was proposed to run from Greater Noida to Agra via Mathura. Amidst issues concerning land acquisition, and various protests and litigations, the deadline for completion of the project had extended beyond its original completion date of February 8, 2010, to April 2013. Meanwhile, the project cost had escalated from Rs 2500 crore (cr) in 2000 to about Rs 10,000 cr as of December 2010. By then, about 80 per cent work on the expressway had been completed. The project was finally expected to be completed around April 2011. This was, however, subject to the pending court judgements and mitigation of risks as perceived by Jaypee Infratech, the concessionaire of the project.
Originally published in Raghuram, G., & Mehta, P. (2011). The Yamuna Expressway. CIPR0009. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mayawati, Ms; Yamuna Expressway; Jaypee Infratech; Express highways -- India; Uttar Pradesh (India); Delhi (India); Agra (India); Greater Noida (India); Mathura (India)